REALISM real-time hand gesture interface for surgeons and medical experts - Achacon, David Louis Jr. M.; Carlos, Denise M.; Puyaoan, Maryann Kaye. (2009)
REALISM: Real-Time Hand Gesture Interface for Surgeons and Medical Experts is a vision based system aiming to provide a non-contact human-computer interaction through hand gestures captured by computer camera. This project is intended for viewing MRI, PET and CT images during medical procedures where surgeons are restricted from any contact to any non sterile device. The common practice of delegating an assistant who controls the mouse or keyboard while the doctor instructs him what to do is slow and awkward. REALISM offers direct control over these digital medical images to surgeons through their hand gestures. We visualize this project with a medical expert in front of a camera performing hand gestures which the computer then interprets as commands for navigation of images. Image navigation (next and previous), zoom in and out and scroll (up, down. left and right) are the primary functions that REALISM intends to provide. The implementation of REALISM is divided into three parts: Hand Detection, Hand Gesture Recognition, and Hand Tracking. The Gesture Vocabulary was designed considering factors such as gesture's ease of use, simplicity and intuitiveness for the users. The system was developed using Java, C and OpenCV. Experiment results show favorable precision and recall in a well lighted environment both on hand detection and hand recognition capability of the system. Given a different set of gesture vocabulary, this study can be extended to other fields and researches such as gaming.
With user manual (bound with the main text).
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Computer software; REALISM (Computer program).; hand gesture interface; computer programs for medical experts